SEARCH FOR MAGNETIC MONOPOLES WITH THE SOUDAN-2 DETECTOR - Thron, J; Allison, W; Alner, G; Ambats, I; Ayres, D; Balka, L; Barr, G; Barrett, W; Benjamin, D; Border, P; Brooks, C; Cobb, J; et al. (1992)
A search for grand unified theory magnetic monopoles making highly ionizing tracks in argon gas has been conducted using the Soudan 2 nucleon decay detector. This underground detector is a large fine-grained tracking calorimeter comprised of long drift tubes read out by proportional wires. No monopole candidates were observed in data taken over almost three years, yielding an upper flux limit of 8.7 × 10-15 cm-2s-1sr-1 for monopole velocities of >2×10-3. © 1992 The American Physical Society.